(untitled) (Journal of the College of Basic Education, 2022)
The climate was not stable and constant in a region of the earth throughout the geological and human history of the earth. Humidity if it is dry, or towards warmth if it is cold, or towards coldness if it is warm). climate in the natural environment and the geographical environment. (15)